Evidence of vertical transmission of Zika virus in field-collected eggs of Aedes aegypti in the Brazilian Amazon. - Cristiano Fernandes da Costa; Arlesson Viana da Silva; Valdinete Alves do Nascimento; Victor Costa de Souza; Dana Cristina da Silva Monteiro; Wagner Cosme Morhy Terrazas; Ricardo Augusto Dos Passos; Suzete Nascimento; José Bento Pereira Lima; Felipe Gomes Naveca (Public Library of Science (PLoS), 2018)
BACKGROUND:Arboviruses are viruses transmitted to humans and other animals by the bite of hematophagous arthropods. Infections caused by chikungunya virus (CHIKV), dengue virus (DENV), Zika virus (ZIKV), and the deadlier yellow fever virus (YFV) are current public health problems in several countries, mainly those located in tropical and subtropical regions. One of the main prevention strategies continues to be vector control, with the elimination of breeding sites and surveillance of infested areas. The use of ovitraps for Aedes mosquitos monitoring has already demonstrated promising results, and maybe be also useful for arboviral surveillance. METHODS:This work aimed to detect natural vertical transmission of arboviruses in Aedes aegypti and Aedes albopictus. Mosquito egg collection was carried out using ovitraps in Itacoatiara, a mid-size city in Amazonas state, Brazil. Collected eggs were allowed to hatch and larvae were tested for CHIKV, DENV, and ZIKV RNA by RT-qPCR. RESULTS:A total of 2,057 specimens (1,793 Ae. aegypti and 264 Ae. albopictus), in 154 larvae pools were processed. Results showed one positive pool for CHIKV and one positive pool for ZIKV. The active ZIKV infection was further confirmed by the detection of the negative-strand viral RNA and nucleotide sequencing which confirmed the Asian genotype. The Infection Rate per 1,000 mosquitoes tested was assessed by Maximum Likelihood Estimation (MLE) with 0.45 and 0.44 for CHIKV and ZIKV, respectively, and by Minimum Infection Rate (MIR) with 0.45 for both viruses. CONCLUSION:To our knowledge, this is the first detection of ZIKV in natural vertical transmission in the Ae. aegypti, a fact that may contribute to ZIKV maintenance in nature during epidemics periods. Furthermore, our results highlight that the use of ovitraps and the molecular detection of arbovirus may contribute to health surveillance, directing the efforts to more efficient transmission blockade.